AB0473 "HALO SIGN" IN ULTRASOUND OF TEMPORAL, FACIAL AND AXILLARY ARTERIES: ASSOCIATIONS WITH CLINICAL SYMPTOMATOLOGY AND LABORATORY FINDINGS. (13th June 2020) - Evangelatos, G.; Fragoulis, G. E.; Iliopoulos, A.
Abstract : Background: Giant cell arteritis (GCA) has two subtypes, the cranial form ("cranial GCA") and the large-vessel form ("LV-GCA"). GCA can present with "cranial" symptoms (headache, visual symptoms, jaw claudication, scalp tenderness), constitutional symptoms (fever, fatigue), limb claudication and symptoms of polymyalgia rheumatica (PMR) and usually causes increased inflammation markers, anemia and thrombocytosis. Ultrasound (US) of the temporal and axillary arteries has a well-established role in cranial GCA and LV-GCA diagnosis, respectively. However, it is unknown whether specific clinical and laboratory parameters are linked with US findings suggestive of vascular inflammation ("halo" sign). Objectives: The aim of this study was to examine possible association between clinical and laboratory characteristics of the patients and detection of vessel wall inflammation in the US. Methods: Patients ≥50 years old with elevated ESR (≥50mm/h) and/or CRP (≥10mg/L) that presented in our outpatient rheumatology clinics from July 2017 to December 2019 with possible clinical diagnosis of GCA were included. Three groups were compared: Patients with "cranial symptoms" (with or without PMR), patients with PMR symptoms only and patients with increased inflammation markers without specific symptoms indicative of GCA. Temporal arteries and their main branches, as well as facial and axillary arteries were evaluated by US bilaterally for the presence of non-compressible "halo sign" at the vessel wall. Clinical symptomatology and the occurrence of anemia and thrombocytosis were recorded. Results: 52 patients were included. 71.2% were females, with a mean±SD age of 71.0±10.0 years. 17 patients had "cranial symptoms" (seven patients with concomitant PMR and ten without), 17 patients had PMR symptoms only, while 18 patients had non-specific symptoms (e.g. fever) (Table 1). Among 17 patients with "cranial symptoms", 7/7 (100%) with concomitant PMR had a positive temporal US, while only 3 out of 10 (30%) without PMR had a positive temporal US (p<0.01) and US was indeterminate in 2 of them (20%). Collectively, 10/17 (58.8%) of patients with "cranial symptoms" and systemic inflammation had a US examination compatible with GCA. No patient with "cranial symptoms" had a positive US of axillary arteries. No patient with only PMR symptoms, had "halo sign" in temporal and facial arteries, while 3 out of 17 (17.6%) had a positive axillary US. From the 18 patients with elevated ESR/CRP, one had a positive temporal US and another one had a positive axillary US. Regarding specific symptoms, positive temporal US was associated with new headache (p=0.003), vision impairment (p=0.001), jaw claudication (p=0.05), scalp tenderness (p=0.01) and fever (P=0.002), but not with PMR (p=0.317). Thrombocytosis was associated with an increased risk for "halo sign" detection in temporal (p=0.04) and facial (p=0.007) arteries, but not in axilliary arteries (p=0.52). Conclusion: 60% of patients with "cranial symptoms" and elevated inflammation markers have US temporal findings indicative of GCA. This is more pronounced in patients with concomitant PMR symptoms and is associated with specific symptomatology. 18% of patients with only PMR symptoms might have LV-GCA, while those with high ESR/CRP without GCA-related symptoms rarely have "halo sign" in US. Disclosure of Interests: None declared